Análisis de las habilidades blandas y su contribución al desempeño laboral en el Hospital Aníbal González Álava período 2022 - Alcívar Hidalgo, Karen Lourdes (2023)
This research work was carried out with the objective of analyzing soft skills and their contribution to the work performance of the Dr. Aníbal González Álava Hospital during the period 2022, to improve the service it offers to citizens from an administrative approach. The study was non-experimental, it was based on an inductive, deductive and analytical-synthetic approach, using interviews and surveys as techniques to obtain data and analyze the relationship between soft skills and job performance at the Aníbal González Álava Hospital. The field and bibliographic research provided relevant and truthful information on soft skills, and the questionnaire and Google Forms facilitated efficient data collection. The main results show a general positive perception in soft skills, such as work comfort, self-esteem and sense of usefulness. However, there are areas for improvement in professional growth, managing differences of opinion, and promoting communication and empathy. Performance evaluations have been mostly positive, but the relationship between soft skills and job performance needs to be studied more. A lack of orientation for new collaborators is evident, affecting their adaptation. In addition, it is necessary to improve feedback, recognition and balance between work load and personal life. In conclusion, an improvement plan is proposed focused on strengthening the soft skills of the staff. It is recommended to promote theoretical understanding through strategies and activities; the implementation of these improvements can increase the quality of work performance.